Determinants of Anti-Corruption Disclosure in Infrastructure Sector Companies Listed on The BEI - Karunia Eri Fitriyanah; Harti Budi Yanti (Eduvest - Journal of Universal Studies, 2025)
The purpose of this study is to examine the influence of company size, government ownership, and foreign ownership on anti-corruption disclosure in infrastructure sector companies listed on the Indonesia Stock Exchange in 2023. The sample was selected using the purposive sampling method with final samples consisting of 64 companies. The content analysis method is used to collect anti-corruption disclosure information in annual reports and corporate sustainability reports. This study uses 40 statement items grouped into 7 themes to measure the extent of corporate anti-corruption disclosure. The results of the study show that company size and government ownership have a positive effect on anti-corruption disclosure. Meanwhile, foreign ownership has no influence on anti-corruption disclosure. This study contributes to the literature by providing a comprehensive overview and determining factors for anti-corruption disclosure in infrastructure sector companies in the lens of legitimacy and institutional theory.